If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 = 13 + 2x Reorder the terms: -3 + 6x = 13 + 2x Solving -3 + 6x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 6x + -2x = 13 + 2x + -2x Combine like terms: 6x + -2x = 4x -3 + 4x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 4x = 13 + 0 -3 + 4x = 13 Add '3' to each side of the equation. -3 + 3 + 4x = 13 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 13 + 3 4x = 13 + 3 Combine like terms: 13 + 3 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 9[y]=27 | | 3/5,4/9,11/15 | | [y]2=28 | | -5[y]=-25 | | (3x-4)(2x+3)=0 | | x=137-173 | | 173-137= | | 17-x=1/3(21) | | 3t-8/2=4t | | 4m^2-11m-45=0 | | 3t-9/2 | | 7.2*10^4/9.4*10^-11 | | 5w+9.9=4.9+8w | | 5m^2-34m-48=0 | | 3(x+2)+27=60 | | x+2/x-3 | | (3x^2-5x-6)+(5x^2+4x+4)= | | 7y^2+51=0 | | 1.2(b-10)=50 | | 4+3x=8x+24 | | 4t+14=6t/5 | | 7x-3=4x-9 | | 5x-12/-3=-6 | | 7w-3w=2(3w+11) | | -6=m-2 | | 82=-2+6(v+6) | | -6=m | | 4y+7y=-99 | | -3=n | | 4a+6=90 | | m-3=21 | | -2y+5.2x=2 |